Surgical Approaches to Benign Parapharyngeal Space Tumors-5-Year Experience - Keyvan Aghazadeh; Mohammadtaghi Khorsandi; Mohamamadjavad Rikhtegar; Amirsina Sharifi; Arsalan Hashemiaghdam; Arezou Hashem Zadeh (Iranian Journal of Otorhinolaryngology, 2020)
Introduction: Various surgical approaches to parapharyngeal space (PPS) tumors are introduced to obtain complete removal with the preservation of the surrounding structures in parapharyngealneoplasms. Here, we will discuss the main techniques and their outcome.   Materials and Methods: This retrospective study was conducted on 78 patients undergone either transoral, transcervical or a combination of these two approaches for the resection of PSS tumors from January 2010 to January 2015. Results: A number of 33 male and 45 female patients with the mean age of 40.9 ± 9.1 were evaluated. 42.3% of the patients were asymptomatic at the initial presentation. Pleomorphic adenoma and schwannoma were a permanent diagnosis in 61(78.2%) and 11(14.1%) patients, respectively. PPS tumors were resected using transoral, transcervical and combined approaches in 35(44.8%), 33(42.3%) and 10 (12.9%) cases, respectively. Recurrence occurred in 10 patients all of whom had apre-styloid pleomorphic adenoma, operated transcervical (P< 0.0001).Three cases of tenth nerve palsy occurred in schwannomas which were operatedtranscervically (P=0.04). Mean hospital stays were 2.11,3.69, and 4.9 days after transoral, transcervical and combined approaches, respectively (P= 0.001). Conclusion: Transoral, transcervical and combined approaches are all able to provide adequate visualization with comparable outcomes.